Synergies Between Knowledge Engineering and Software Engineering - Nalepa, Grzegorz J.; Baumeister, Joachim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book compiles a number of contributions originating from the KESE (Knowledge Engineering and Software Engineering) workshop series from 2005 to 2015. The idea behind the series was the realignment of the knowledge engineering discipline and its strong relation to software engineering, as well as to the classical aspects of artificial intelligence research. The book introduces symbiotic work combining these disciplines, such as aspect-oriented and agile engineering, using anti-patterns, and system refinement. Furthermore, it presents successful applications from different areas that were created by combining techniques from both areas.
Aspect-Oriented Ontology Development -- Similarity-based Retrieval and Automatic Adaptation of Semantic Workflows -- Development of knowledge-based systems which use Bayesian networks -- Knowledge Acquisition during Software Development: Modeling with anti-patterns -- Knowledge Engineering of System Refinement -- Using the Event-B Formal Method and the Rodin framework for Verification the Knowledge Base of an Rule-Based Expert System -- Knowledge Engineering for Distributed Case-Based Reasoning Systems -- Knowledge engineering for decision support on diagnosis and maintenance in the aircraft domain -- OntoMaven - Maven-based Ontology Development and Management of Distributed Ontology Repositories -- References.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence